Limo Zine. (s.l. : s.n., 2022)
Vonckx, Rik ; Triolo, Antonino ; Cartrysse, Quinten ; Bellinkx, Ruben ; Huyghe, Bert ; De Keyzer, Louis ; Faes, Xander ; Janssens, Sybren ; Erdemir, Gunbike ; Steenbakkers, Eva ; Laute, Vincent ; Hoeben, Chris ; Rocoeur, Louis ; Lunato, Ben ; Servaes, Bavo ; Rogiest, Laurens ; Elpidia, Ludovica ; Legrand, Hannes ; De Weerdt, Ian ; Goossens, Antoine ; Boone, Casper ; Aristidou, Sophia ; Beumer, Anne ; Kerckhove, Emil ; Margodt, Nello ; Smis, Steven ; Van Daele, Liselotte
boek